The Role Of Creatine Supplementation In Enhanching Cognitive Function In The General Population: A Literature Review: A Literature Review - Gala Novendra (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Background: Creatine is a vital compound in cellular energy homeostasis, playing a key role in regenerating adenosine triphosphate (ATP) in tissues with high energy demands, such as the brain. Due to its importance in cerebral bioenergetics, creatine supplementation has been investigated as a potential cognitive enhancer. This literature review aims to synthesize and evaluate the current evidence on the effects of creatine supplementation on cognitive function in the healthy general population. Methods: A systematic search was conducted on PubMed and Google Scholar for articles published between 2015 and 2025. The search strategy utilized the PICO framework (Population: healthy adults; Intervention: oral creatine monohydrate; Comparison: placebo; Outcome: cognitive function) and specific keywords, including